Flexible life annuities - Alexis Direr (Center for Economic Studies and ifo Institute (CESifo), 2007)
Annuity contracts typically deliver a stream of income at a predetermined level in order to insure against the risk of longevity. This paper explores whether flexible annuities, which give subscribers the possibility to choose between different levels for their annuities, may be welfare enhancing. In the case where agents gradually discover their actual probability of survival, a predetermined and one-size-fits-all annuity plan is optimal. If an expenditure risk is added along with the longevity risk, a flexible annuity plan is better even though the consumption path cannot be isolated from uninsured expenses anymore.
Keywords: E21; D82; 330; Alterssicherung; Sterblichkeit; Risikopräferenz; Agent-based Model; Vertragstheorie